Paramedics' Newborn Life Support Knowledge and Skills Before and After a Targeted Simulation-Based Educational Intervention - Lukas P. Mileder; Jennifer Gressl; Berndt Urlesberger; Wolfgang Raith (Frontiers Media S.A., 2019)
Objective: Resuscitation of neonates after birth in the out-of-hospital setting is challenging. Thus, we aimed to assess paramedics' newborn life support knowledge and skills before and after targeted simulation-based training.Methods: Voluntary paramedics were recruited from a single Red Cross division. During a 1-day simulation-based educational intervention, essential aspects of neonatal resuscitation were taught and practiced. Before and after simulation-based training, we assessed (1) knowledge of current European Resuscitation Council (ERC) guidelines using a 20-item-questionnaire and (2) the quality of simulated bag-valve-mask ventilation by measuring face mask leakage, using a respiratory function monitor (Standardized Measurement of Airway Resuscitation Training [SMART], GM Instruments Ltd., United Kingdom).Results: Forty-one paramedics participated in the initial survey and 12 took part in the simulation-based educational intervention. There was a significant increase in the number of correctly answered questions: median 62.1% (IQR 37.5-77.4%) vs. 91.7% (IQR 83.3-100%; p = 0.001). A total of 1,332 inflations were analyzed. The incidence of substantial mask leakage >75% decreased significantly after training (15.8 vs. 6.1%; p < 0.001), while median mask leakage was similar (17.0% [IQR 0.0-55.0%] vs. 18.0% [IQR 6.0-34.0%]; p = 0.414).Conclusions: Among paramedics, theoretical knowledge of current ERC guidelines was moderate in this study. Participation in a targeted simulation-based educational intervention was associated with a significant increase in theoretical knowledge. The initially high incidence of substantial mask leakage >75% was decreased after simulation-based training using respiratory function monitoring.